Developing and validating utility parameters to establish patient-reported outcome-based perioperative symptom management in patients with lung cancer: a multicentre, prospective, observational cohort study protocol. Issue 10 (28th October 2019) - Dai, Wei; Xie, Shaohua; Zhang, Rui; Wei, Xing; Wu, Chuanmei; Zhang, Yuanqiang; Feng, Wenhong; Liao, Xiaoqing; Mu, Yunfei; Zhou, Heling; Cheng, Xuemei; Jiang, Yanhua; et al.
Abstract : Introduction: Patient-reported outcome-based symptom monitoring and alerting have been attractive for patient care after a tumour-removal surgery. However, the implementation parameters of this patient-centred symptom management system in perioperative patients with lung cancer are still lacking. We aim to develop a perioperative symptom scale (PSS) for monitoring, to determine the optimal time points for symptom assessment and to define the alert thresholds for medical intervention. Methods and analysis: This study will prospectively recruit 300 patients undergoing lung cancer surgery in six hospitals. The MD Anderson Symptom Inventory–Lung Cancer Module (MDASI-LC) is used to collect longitudinal symptom data preoperatively, daily postoperatively during in-hospital stay and weekly after discharge until 4 weeks or the start of postoperative oncological therapy. Symptoms that change significantly over time will be generated as the PSS. We will determine the optimal time points for follow-up using the generalised linear mixed-effects models. The MDASI-LC interference-measured functional status will be used as the anchor for the alert thresholds. Ethics and dissemination: Ethics Committee of Sichuan Cancer Hospital approved this study on 16 October 2017 (No. SCCHEC-02-2017-042). The manuscript is based on the latest protocol of Version 3.0, 15 September 2019. The results of this study will be presented at medical conferences and published in peer-reviewed journals. Trials registration number: NCT03341377 .